My Home Is My Stage: Restaurant Experiences in Two Estonian Lifestyle Enterprises - Ester Võsu; Anu Kannike (Journal of Ethnology and Folkloristics)
This article discusses recent developments in the home-based lifestyle business featuring the example of two cases: Tammuri farm restaurant near Otepää in South Estonia, and home restaurant MerMer in Kolga-Aabla in North Estonia. We study the restaurants from a Goffmanian performance perspective, focusing on the lifestyle entrepreneur's viewpoint of creating a restaurant experience in their homes. Accordingly, the home and its surroundings are considered a setting in which food has an important role as a performance medium and multiple roles are enacted by a single entrepreneur as a performer. Freshness, quality and locality of food, homeliness and personalised service are used for creating a special home restaurant meal experience. The two cases also shed light on the dynamics of the concepts of home and lifestyle entrepreneurship in contemporary Estonia, challenging the understanding of restaurant cuisine and home cooking as oppositional practices of food preparation and consumption.